INVESTIGATING THE IMPLEMENTATION OF GAMIFICATION APPROACH TO ENHANCE STUDENTS LEARNING ENGAGEMENT - Sean Patrick Kang; Michael Recard (Journey: Journal of English Language and Pedagogy, 2023)
This research aims to investigate the effectiveness of thegamification approach in enhancing students learning engagement through the utilizations of gamified learning application such as Quizziz under iB Curriculum. Also, to find how significance is the role of teacher while implementing the gamification approach. There were three cycles to obtain qualitative data—planning stage, action stage and observation stage, taken from seven male and fourteen female students. The instruments are observation note from the cooperating teachers and field notes. After that they were analyzed and classified with the rules and procedures, the implementation, and the benefits of the implementation. The study shows that the implementation of gamification demonstraded significance impact in enhancing students’ learning engagement. It was found that the enhancement of students’ learning engagement through gamification approach should consider the time frame of the lesson, students’ personality, clear instructions in line with the rules and procedures, and frequent check for understanding as the students could contribute to the lesson. Further, the teacher’s role was significant to guide the students through discussions in understanding the learned concepts. It is recommended in future research to have longer implementation period to compare the effectiveness during online and hybrid learning, and to elaborate different gamified learning platforms.